PO264 Prevalence of atrial fibrilation in 395 patients presenting with ocular ischaemic events. (1st December 2017) - Zarkali, Angeliki; Cheng, Amanda; Dados, Agnes; Simister, Robert; Chandratheva, Arvind
Abstract : Introduction: Atrial fibrillation (AF) in patients with ischaemic ocular events is often under-investigated. We aimed to determine the prevalence of AF in these patients. Setting: University College Hospital London daily TIA clinic, main referral centre for North-Central London. Consecutive records for all patients with transient or permanent ischaemic visual loss were reviewed, January 2014-September 2016. Electrocardiograms (ECG), cardiac monitoring reports and previous AF were recorded. Results: Of 395 patients, 220 (55.4%) male, mean age 64 years (SD=15.1), 261 (66%) had transient and 134 (34%) permanent events. ECG was performed in 360 (91%) but only 236 (60%) had cardiac monitoring; 386 (91.1%) had carotid imaging. 8% (31) had AF and 8% (31) symptomatic carotid disease (CAS). Median ABCD2 in AF was 3, similar to non-AF patients. Only 51.6% with known AF were anticoagulated. Hypertension (p=0.012), previous TIA (p<0.001) and stroke (p=0.014) were more common in AF patients; diabetes (p=0.793), smoking (p=0.653) and hypercholesterolaemia (p=0.144) were not. 90 day recurrence of stroke/TIA/ocular ischaemia was 10.1%. This was higher in AF patients (16.1%, mean 12.3 days), comparable to CAS patients (18.9%). AF patients were more likely to represent with stroke (HR=5.74, 95%CI=[0.54, 61.6], p=0.239). Conclusion: 8% of patients with ischaemic ocular events had AF, same as CAS; this is probably an underestimate, as these patients are often under-investigated with only 60% undergoing cardiac monitoring.